Policy Reforms and Institutional Weaknesses: Closing the Gap - Gilberto M. Llanto; Eduardo T. Gonzalez (Philippine Institute for Development Studies (PIDS), 2007)
The promise and potential of the Philippine economy has remained unrealized notwithstanding the country's talented labor force, skilled professionals, and relatively abundant resources. What ails the Philippines? This paper argues that the incompetence and downright corruption of Philippine institutions have much to do with the country's dismal performance in economic growth and poverty reduction. It draws attention to the significance of effective institutional and regulatory frameworks in orchestrating the policy development process and the need to create competent institutions to nudge such process in the direction of implementing better policies, examines strategic triggers for reform while the final section explores institutions and strategies to support the policy development process.
Keywords: 330; governance; regulatory framework; rule of law; policy development process; effective institutions; accountability; Good Governance; Institutionelle Infrastruktur; Rechtsordnung; Entwicklungspolitik; Philippinen